The effects of earthworm concentration and extraction time on solubility of protein - Nur Hidayat; Reny N. Utami; Wignyanto Wignyanto (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2018)
Earthworm (Lumbricus rubellus) is known to contain proteins making it suitable for alternative high-protein resources for feed or animal food. Exctraction of proteins from earthworms is not an easy task and it requires multiple steps for purifying the protein extract. Furthermore, the extraction of earthworm protein is considered as uneconomical due to high operational cost. Therefore, altering the process is necesarry to enhance the extraction. The objective of this research is to optimize the solubility of protein from earthworm juice. The design used in this research is a completely randomized design consisting of two factors which are A (earthworm concentration) and B (extraction time). The results show that solubility of protein was 28.12% and the soluble solid was 67.63%. The optimum process includes earthworm concentration of 15% and extraction time of 90 minutes.